Identification of a novel SDHB c.563 T > C mutation responsible for Paraganglioma syndrome and genetic analysis of the SDHB gene in China: a case report - Heye Chen; Wei Yao; Qing He; Xuefang Yu; Bo Bian (BMC, 2020)
Abstract Background Pheochromocytoma/paraganglioma (PPGL) is a rare neuroendocrine tumor. Succinate dehydrogenase (SDH) deficiency has been confirmed to be associated with PPGL in various studies. SDHB mutations play an important role in PPGL. However, genetic screening of PPGL patients has not been widely carried out in clinics in China, and only a few related studies have been reported. Case presentation We report a case of a 23-year-old woman with paraganglioma (PGL) caused by a novel missense SDHB mutation, c.563 T > C (p.Leu188Pro), who presented with paroxysmal hypertension. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed a PGL in the right retroperitoneum and no metastasis. The patient was treated with surgical excision and did not have postsurgerical paroxysmal hypertension. In addition, we searched the literature related to variations in SDHB genes in Chinese patients with PPGL using multiple online databases, including PubMed, China Hospital Knowledge Database and Wanfang Data. Ultimately, 14 studies (published between 2006 and 2019) comprising 34 cases of SDHB-related PGL or pheochromocytoma (PCC) were found. In total, 35 patients were enrolled in this study, and 25 mutations were identified. The common genetic alterations of SDHB in China were c.136C > T (11.4%), c.18C > A (11.4%) and c.725G > A (8.5%). Some carriers of SDHB mutations (28.1%) developed metastatic PPGL, and a high frequency of head and neck PGLs (HNPGLs) (59.4%) was reported. Conclusions We describe a classic case with a novel SDHB c.563 T > C mutation. Based on our literature review, common SDHB gene mutations in Chinese PPGL patients are c.136C > T, c.18C > A and c.725G > A.